Effect of zinc versus vitamin A supplementation on pediatric patients with community-acquired pneumonia - Saied, Aya; El Borolossy, Radwa Maher; Ramzy, Mourad Alfy; Sabri, Nagwa A. (Frontiers in Pharmacology, 2022)
Background: Community-acquired pneumonia (CAP) is one of the most common infectious diseases affecting the respiratory tract and is responsible for a high mortality rate in children less than 5 years of age. The mortality rate due to CAP is much higher in low/middle-income countries than in high-income countries due to malnutrition and different micronutrient deficiencies that weaken the immune system. Aim: The aim of this study was to compare the effects of zinc and vitamin A, as two elements of micronutrient agents, on the recovery rate of children suffering from CAP aged from 6 months to 5 years. The length of hospital stays was also investigated. Method: A comparative, randomized, open-label, controlled, interventional study was carried out among children less than 5 years of age in the pediatric intensive care unit (PICU) diagnosed with CAP who were randomly divided into three groups. In addition to the standard therapy, group 1 was given zinc, group 2 was given vitamin A, and group 3 was the control group, given the standard therapy only. We compared the three groups in terms of recovery rate and hospital stay. Result: The duration of hospitalization following zinc and vitamin A supplementation was reduced by an average of 3.21 days (95% CI: 5.01–1.41, p = 0.01) and 2.43 days (95% CI: 4.29–0.57, p = 0.01), respectively, compared to the control group. In addition, the two groups of vitamin A and zinc supplementation were associated with a shorter duration of pneumonic effusion (p < 0.001) in comparison to the control group. Additionally, there was no significant difference between the effects of zinc and vitamin A when compared to each other in terms of duration of hospital stay and pneumatic effusion. Conclusion: The administration of zinc or vitamin A supplementation proved to be useful as an add-on therapy in community-acquired pneumonia, where it reduced the length of hospital stay and the duration of pneumonic effusion in pneumonic children less than 5 years of age.